Concerns and Problems of Orthodontic Patients During the COVID-19 Pandemic - Atefe Saffar Shahroudi; Ahmad Sodagar; Ahmadreza Shamshiri; Samar Rahimpour; Seyed Morteza Samimi (Tehran University of Medical Sciences, 2022)
Objectives: We aimed to find the main concerns of patients undergoing active orthodontic treatments and their orthodontic treatment-related (OTR) problems during the coronavirus disease-2019 (COVID-19) pandemic. Materials and Methods: A researcher-made questionnaire addressing several aspects of the effects of COVID-19 pandemic on treatment was distributed among 181 orthodontic patients receiving active treatment. Anxiety, concern, problems, and willingness to attend orthodontic appointments and to undergo other dental procedures was questioned. The correlation of gender, age, COVID-19-related anxiety and OTR anxiety was statistically analyzed. Patient satisfaction level with different aspects of dental-clinic performance was also evaluated. Results: The participants included 117 females and 64 males, of which 94% adhered to the pandemic restrictions. The mean COVID-19-related- and OTR-anxiety were 51.7% and 52.7%, respectively. Higher COVID-19-related anxiety was significantly correlated with higher OTR anxiety (P<0.001). There was an inverse correlation between general COVID-19-related anxiety and OTR anxiety and willingness to attend orthodontic appointments (P<0.05). A positive insignificant (P=0.07) correlation existed between age and willingness to attend appointments. The main concern was prolongation of treatment and the most common problem was irritation of oral soft tissues by appliances. The majority (65.3%) were willing to attend their orthodontic appointments. Orthognathic surgery (62%) had the highest while, dental restorations and radiography had the lowest refusal rates (9.9%). Conclusion: COVID-19 pandemic significantly affected orthodontic treatment. The level of COVID-19-related anxiety was moderately high and patients were concerned about the impact of lockdown on their orthodontic treatment outcome. Young adults demonstrated higher levels of stress than other age-groups.